The Voltage-Ear – An Anomaly in photovoltaic systems with undersized inverters - Wittmann, Ernst; Buerhop-Lutz, Claudia; Christlein, Vincent; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (IEEE Photonics Journal, 2024)
This study presents a phenomenon in photovoltaic field installations we call voltage ear. PV installations exhibit the voltage ear under specific conditions where modules generate more power than the inverter can handle. When inverters exceed their power limit it results in inverter clipping, and the solar modules are regulated to operate at a voltage above that at maximum power. This kind of voltage rise leads to a specific pattern in the monitoring data – the voltage ear. In the present study, data from a solar park in France was analyzed. This park featured a high rate of inverter malfunctions, including overheating and fires, resulting in an estimated 5% failure rate and, ultimately, in a complete replacement of inverters. An automated analysis of the monitoring data revealed 32.000 occurrences of excess voltage in 1.65 million data points (2%). Instances of the phenomena were detected and segmented using a K-means sorting algorithm, which yielded a perfect recall value. Analysis of the identified voltage ear conditions showed, that it occurs predominantly during seasons of high irradiance and cool temperatures. Excess voltages of up to 161 V in single strings were observed, increasing the probability for PID and inverter damage. The direct yield loss due to deviation from maximum power point was between 0.02% in January and 0.9% in June. We assume, that the voltage ear is a symptom of system design issues that can result in malfunctioning of inverters and hope that it will be useful as an indicator for identifying design and operation issues.<br
Keywords: Inverters; Ear; Voltage measurement; Monitoring; Voltage control; Temperature measurement; Current measurement; PV field inspection; monitoring data; voltage ear; K-means clustering; inverter failure